Kualitas Pelayanan Kesehatan Puskesmas Singandaru di Kota Serang Pada Era New Normal - Nikki Prafitri Prafitri (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
The quality of public services is the suitability of service delivery between the expectations of service users and the service standards. The Singandaru Health Center is one of the health centers in Serang City that experienced a decline in the community satisfaction index during the pandemic. Thus, this study aims to determine the service quality of Singandaru Health Center in the new normal era. The method used in this research is a qualitative research method. The results showed that the quality of health services in the new normal has been running effectively. This is due to the commitment of service officers in information transparency, initiative and commitment of leaders and officers in carrying out service announcements, responsiveness of officers who are fast in responding to complaints, good supervision from leaders, understanding and awareness of officers about information and socialization of the service flow so that the public know their obligations as well as service users. However, online services have not run optimally due to the lack of human resources that focus on supporting the implementation of IT in health services.